2023
DOI: 10.3847/1538-4357/acbf2e
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Shapes of the Line-of-sight Velocity Distributions in Massive Early-type Galaxies from Nonparametric Spectral Models

Abstract: We present the first systematic study of the detailed shapes of the line-of-sight velocity distributions (LOSVDs) in nine massive early-type galaxies (ETGs) using the novel nonparametric modeling code WINGFIT. High-signal spectral observations with the Multi-Unit Spectroscopic Explorer (MUSE) at the Very Large Telescope allow us to measure between 40 and 400 individual LOSVDs in each galaxy at a signal-to-noise ratio level better than 100 per spectral bin and to trace the LOSVDs all the way out to the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…The kinematic structure of NGC 5419 can be well explained by the triaxial models (averaged over both sides we get χ 2 /N data = 0.45). As already visible in the SALT stellar kinematics (Mazzalay et al 2016) but much more clearly revealed by the MUSE observations (Mehrgan et al 2023), the velocity map of NGC 5419 points to a kinematically distinct core (KDC). We will come back to the KDC in Section 4.5.…”
Section: Kinematic Recoverymentioning
confidence: 54%
See 4 more Smart Citations
“…The kinematic structure of NGC 5419 can be well explained by the triaxial models (averaged over both sides we get χ 2 /N data = 0.45). As already visible in the SALT stellar kinematics (Mazzalay et al 2016) but much more clearly revealed by the MUSE observations (Mehrgan et al 2023), the velocity map of NGC 5419 points to a kinematically distinct core (KDC). We will come back to the KDC in Section 4.5.…”
Section: Kinematic Recoverymentioning
confidence: 54%
“…Moreover, the 2D velocity pattern resembles a kind of "yin-yang symbol" on the sky caused by an apparent connection between the velocity pattern of the KDC and its surrounding large-scale velocity field. The connections between the red and blue inner and outer velocity structures, which cause the similarity to a yin-yang symbol, become even more apparent with the finer bins of Mehrgan et al (2023).…”
Section: Origin Of the Kinematically Distinct Corementioning
confidence: 98%
See 3 more Smart Citations